Immunoglobulin G4-related periodontitis: case report and review of the literature - Jinmei Zhang; Lei Zhao; Jieyu Zhou; Wei Dong; Yafei Wu (BMC, 2021)
Abstract Background Immunoglobulin G4-related disease (IgG4-RD) is a chronic inflammatory systemic disease of unknown etiology that can affect one or multiple organs. The disease can mimic many infectious and inflammatory diseases, mainly causing organ enlargement or hyperplasia. Its diagnosis primarily relies on clinical, serologic, and histological features (lymphoplasmacytic infiltrates, storiform fibrosis, and obliterative phlebitis of IgG4 + plasma cells). Here, we report a rare case of IgG4-related periodontitis, and review the relevant literatures. Case presentation A 38-year-old Chinese man visited the Department of Periodontics with gingival enlargement, loose teeth, and tooth loss. The patient had very poor oral hygiene and a large amount of calculus. Gingivae were edematous with deep periodontal pockets and attachment loss. Panoramic radiography showed alveolar bone loss. Serologic examination showed that IgG was 23.70 g/L and IgG4 concentration was 2.800 g/L. There was significant lymphoplasmacytic infiltration, a storiform pattern of fibrosis, and mitotic figures with hematoxylin and eosin staining; immunohistochemical staining showed 10 scattered IgG4-positive plasma cells in a high-power field. The patient was diagnosed as IgG4-related periodontitis. He received a course of corticosteroids with periodontal therapy, and the enlargement was significantly improved without recurrence. Conclusion IgG4-RD in the oral and maxillofacial region mainly involves salivary glands, but this rare case was characterized by enlarged gingivae. The differential diagnosis of IgG4-RD should be based on the clinical features and serologic (IgG4) and histopathological examinations. Corticosteroid therapy is effective for most IgG4-RD patients. Taken together, we hope this case report and the literature review can help dentists to improve their understanding of the IgG4-RD.